Typologia Jonasz – Paweł w narracji o podróży morskiej do Rzymu (Dz 27,13–28,16) - Podeszwa, Paweł (Teologia i Człowiek, 2012)
The article deals with potential typology of Jonah and Paul as undertaken by the author of the Acts of the Apostles (chapters 27–28), describing the Apostle’s voyage to Rome and his subsequent arrival in the capital of the Empire. It starts with a number of remarks about the Book of Acts as paradigmatic historiography. The next point is devoted to discussing the main literary techniques utilized by Luke, with particular emphasis on typology. It is then followed by an analysis of the typology of Jonah and Paul as well as its paradigmatic and theological significance. The typology being used enables Luke to show Paul as a prophet of Jesus. The typology also serves to convey the idea of universalism characterizing the Apostle’s prophetic mission. Just as Jonah was sent by God to a pagan city of Nineveh, now Paul, by God’s will, becomes the apostle and prophet of both Jews and Gentiles. He fulfils his mission courageously thus bringing salvation to those who are ready to listen to His word.